Aspek Reproduksi Ikan Tetet, Johnius belangerii Cuvier (Pisces: Sciaenidae) Di Perairan Pantai Mayangan, Jawa Barat - Mohammad Fadjar Rahardjo; Charles Parningotan Haratua Simanjuntak (Jurnal Perikanan Universitas Gadjah Mada, 2007)
The objective of the experiment was to know the effect of vitamin C on gonadal development of giant freshwater prawn (Macrobrachium rosenbergii) broodstock. Female broodstock of 30-60 g and male broodstock of 40-70 g average body weight were used in this experiment. The broodstock were fed with different dose of vitamin C in feed as 0; 0.05; 0.10; and 0.15% at 3-4% of biomass weight per day for 3 months. Gonado Somatic Index (GSI) value obtained from the diet with 0.15% of vitamin C was significantly different from others (P0.05). The supplementation of vitamin C in the diet of giant freshwater prawn broodstock is important for gonadal development.